2019
DOI: 10.1177/0885066619885838
|View full text |Cite
|
Sign up to set email alerts
|

Six-Minute Walk Distance After Critical Illness: A Systematic Review and Meta-Analysis

Abstract: Background and Objectives: Impaired physical functioning is common and long lasting after an intensive care unit (ICU) admission. The 6-minute walk test (6MWT) is a validated and widely used test of functional capacity. This systematic review synthesizes existing data in order to: (1) evaluate 6-minute walk distance (6MWD) in meters over longitudinal follow-up after critical illness, (2) compare 6MWD between acute respiratory distress syndrome (ARDS) versus non-ARDS survivors, and (3) evaluate patient- and ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 46 publications
8
60
5
Order By: Relevance
“…Our finding that exercise capacity was limited at 3, 6, and 12 months after ICU discharge was similar to the results of Fan et al who reported impairment in 6MW distance in survivors after acute lung injury, 6 and also were comparable to the findings of Herridge et al in survivors of ARDS, one year after ICU discharge 33 . However, our findings identified more severe limitations in exercise capacity in women compared with men, which agrees with the findings of a recent systematic review and meta‐analysis reporting that the female gender was associated with shorter 6MW distances achieved after critical illness 34 . Furthermore, our women participants had lower self‐reported physical function (SF‐36v2 PF domain) at 3 and 6 months after ICU discharge than patients who were diagnosed with ICU‐AW during their ICU stays 17 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that exercise capacity was limited at 3, 6, and 12 months after ICU discharge was similar to the results of Fan et al who reported impairment in 6MW distance in survivors after acute lung injury, 6 and also were comparable to the findings of Herridge et al in survivors of ARDS, one year after ICU discharge 33 . However, our findings identified more severe limitations in exercise capacity in women compared with men, which agrees with the findings of a recent systematic review and meta‐analysis reporting that the female gender was associated with shorter 6MW distances achieved after critical illness 34 . Furthermore, our women participants had lower self‐reported physical function (SF‐36v2 PF domain) at 3 and 6 months after ICU discharge than patients who were diagnosed with ICU‐AW during their ICU stays 17 .…”
Section: Discussionsupporting
confidence: 91%
“…33 However, our findings identified more severe limitations in exercise capacity in women compared with men, which agrees with the findings of a recent systematic review and meta-analysis reporting that the female gender was associated with shorter 6MW distances achieved after critical illness. 34 tion has been reported between male gender and greater physical recovery after ICU stay. 1,12 Also, an association has been reported between younger women with fewer days of sedation and greater physical recovery compared with three other trajectory groups.…”
Section: Re Sultsmentioning
confidence: 99%
“…The 6MWT was only completed once, without replication. Whilst this is common in studies involving critically ill patients [46], the potential feasibility or impact of learning effects of repeated 6MWT in hospital settings among critical illness survivors remains a priority for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Activity limitations commonly associated with PICS include limited exercise capacity, reduced gait speed, and problems with balance. 6,8 Exercise capacity, as measured by the Six Minute Walk Test (6MWT), is 55% to 84% of predicted or control group values during the first year following critical illness 6,25 and factors associated with reduced exercise capacity include female sex, presence of preexisting comorbidity, and history of acute respiratory distress syndrome. 25 The 6MWT is a robust outcome measure that had been validated for people following ICU care.…”
Section: Screening For Problems Associated With Picsmentioning
confidence: 99%
“…6,8 Exercise capacity, as measured by the Six Minute Walk Test (6MWT), is 55% to 84% of predicted or control group values during the first year following critical illness 6,25 and factors associated with reduced exercise capacity include female sex, presence of preexisting comorbidity, and history of acute respiratory distress syndrome. 25 The 6MWT is a robust outcome measure that had been validated for people following ICU care. 26,27 The 6MWT has been used to assess exercise capacity for people with PICS because of the availability of normative data from the general population that can be used for comparison.…”
Section: Screening For Problems Associated With Picsmentioning
confidence: 99%